Isotopes of amino acids give novel insights on nitrogen sources partitioning and trophic position of invertebrates in a subtropical mangrove. (June 2023) - Thibodeau, Benoit; Allais, Laetitia; Agusto, Laura Elisabeth; So, Mandy Wing Kwan; Cannicci, Stefano
Highlights: We quantified the proportion of vascular vs non-vascular source of nitrogen in the food web of a sub-tropical mangrove. All crabs included vascular (mangrove leaves) into their diet. Niche partitioning between different fiddler crab species were observed for the firt time. Abstract: Mangrove forests are characterised by a specialised fauna with low ecological redundancy. Their faunal diversity is also decreasing across the tropics, with cascading effects on the ecosystem services provided by these forests. Traditional tools often failed to assess the importance of different sources of nutrients and a reliable trophic position estimate in mangroves, although this information is crucial to better advise on effective conservation strategies. Here, we present nitrogen and carbon isotope data of individual amino acids measured in primary producers and fauna inhabiting a subtropical mangrove. We quantified the relative importance of vascular and non-vascular source of nitrogen in the mangrove food web. We found that most gastropods mostly exclusively rely on nitrogen originating from the marine environment (non-vascular) while most brachyuran crabs integrate between 8 and 50% of their nitrogen from vascular sources, most probably by processing decaying mangrove leaves. This highlights the unique role of crabs in processing the low-nutritional mangrove leaves into the food web. Moreover, we estimated the trophic position for 17 invertebrate species inhabiting the mangrove. We highlighted previously unreported difference in term of trophic position and source of food for several species, which were previously thought to have overlapping feeding preferences. Our data thus suggest that the inherent lack of ecological redundancy present in mangrove may even be more severe than predicted by recent estimates.